Port Site Infection after Elective Laparoscopic Cholecystectomy with or without the Use of Prophylactic Antibiotics: A Comparative Cross-Sectional Study - Shakya, Yagya Ratna; Basnet, Samjhana; Giri, Latika; K.C., Ajay; Karmacharya, Robin Man (Journal of Nobel Medical College, 2023)
Background: Laparoscopic surgery, a minimally invasive procedure, has gained popularity due to early recovery rate and minimal incision. Port site infection following laparoscopic surgery is an infrequent complication, increasing patient's morbidity, and also damaging surgeon's reputation. It depends on sterilization and surgical techniques, which have improved with time. The aim of this study is to evaluate the role of prophylactic antibiotics in preventing port site infection after laparoscopic cholecystectomy. Materials and Methods: A comparative cross-sectional study on 200 patients undergoing elective laparoscopic cholecystectomy was conducted from November 2021 to February 2022 in tertiary care Hospital by using systematic random sampling.Among the 200 patients, 100 odd numbered patients were given antibiotics, and 100 even numbered patients were not. The outcome of the two groups was measured with regard to port site infection. Results: The mean age in prophylactic antibiotic receiving group and not receiving group was 42.13 (SD = 14.41) and 42.71(SD = 14.29) years, respectively. The female: male ratio for total patients was 2.77.There were three cases of port site infection in total, in group receiving antibiotics (Cefotaxime), there was one case, whereas in placebo group, there were two. Simple logistic regression was utilized to compare the results of two groups (p>0.05). Similarly, Chi-square test was applied to histopathology diagnosis, which showed no statistically significant difference (χ2 = 0.99, P = 0.80). Conclusion: Antibiotic prophylaxis does not lower the rate of infectious in patients undergoing elective laparoscopic cholecystectomy.